Executive anosognosia in progressive supranuclear palsy versus Parkinson’s disease - Ye, L.; Seidler, L.; Chemodanow, D.; Respondek, G.; Niesmann, C.; Wilkens, I.; Klietz, M.; Höglinger, G. U.; Kopp, B. (Frontiers in Neurology, 2026)
BackgroundExecutive function deficits are common among patients with Parkinson’s disease (PD) and progressive supranuclear palsy (PSP). Executive function refers to higher-order cognitive processes thought to involve fronto-striatal circuits. Some patients with executive deficits may be unable to recognize or report them, a condition we refer to as executive anosognosia.ObjectiveTo conduct a comparative analysis of executive anosognosia in patients diagnosed with PSP and PD.MethodsWe compared an objective neuropsychological assessment (ONA) of composite executive function (ONA-CEF), which includes semantic and phonemic verbal fluency, as well as two sub-scores from the Wisconsin Card Sorting Test, with patient- and informant-reported rating scales. We used the Dysexecutive Questionnaire Revised (DEX-R) to evaluate near-transfer executive complaints and the Aachen Activity and Participation Index: Cognition and Participation (AAPI-CP) composite to evaluate far-transfer cognitive and social difficulties. Discrepancy indices were calculated for patients and informants (ONA-CEF minus DEX-R and ONA-CEF minus AAPI-CP).ResultsPSP patients had significantly larger negative discrepancies than PD patients, indicating stronger executive anosognosia. Although informant reports reduced these discrepancies, significant underreporting persisted in PSP informants. Correlational analyses revealed that patient-reported DEX-R difficulties were strongly correlated with depressive symptoms (r ≈ 0.65) but not with objective executive performance (r ≈ 0.00).ConclusionExecutive anosognosia is a marker of PSP, highlighting the need for objective neuropsychological assessments in clinical trials. PSP patients’ reports of executive dysfunction are more associated with mood than actual impairment, which challenges the validity of patient-reported outcomes in PSP and related neurological diseases.